Retóricas de la raza: intelectuales mexicanos ante la guerra del 98 - Rojas, Rafael (El Colegio de México, A.C., 2000)
The war between Spain and the United States. which broke out in the summer of 1898 in Cuba, Puerto Rico and Philippines -Spain's last three American territories- was passionately followed by all Latin America countries. The old metropolis, which had by then resumed its  relations with the  Hispanic-Arnerican nations, was now facing the new imperial democracy arising in the  late-nineteenth century United States. As a neighboring country, Mexico was almost an eye-witness to all this and lived the war as if it were  being waged on Mexican soil. It was also in Mexico where supporters of Spain and the United States, friends and enemies of Cuban independence, opposed their intellectual and political strength. This paper is about that parallel war fought in 1898 within the culture and politics of the Porliriato.